2020
DOI: 10.2217/rme-2019-0123
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration in Rabbit Calvarial Defects Using Prgf and Adipose-Derived Stem Cells: Histomorphometrical Analysis

Abstract: Aim: The aim of this study was to evaluate the osteogenic potential of adipose-derived stem cells (ADSCs) and to assess the influence of plasma rich in growth factors (PRGF) on bone regeneration using ADSCs. Materials & methods: Bone defects were randomly allocated to the five treatment modalities: spontaneous healing, natural bovine bone mineral (BBM), BBM loaded with PRGF, BBM loaded with ADSCs and BBM loaded with a combination of ADSCs and PRGF. Results: The PRGF significantly enhanced the biomaterial-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Meanwhile, studies showed that the degradation of polylactic acid (PLA) biopolyester materials is relatively fast, while the degradation of polyhydroxyalkanoate (PHA) is relatively slow [20]. And human adipose derived stem cells (hADSCs) as seed cells are also a potential candidate for osteogenesis differentiation [21][22][23][24], which have been obtained more easily from subcutaneous tissue and widely employed in engineered tissue. These studies inspired us to design a novel long-acting BMPs release system based on PLA and PHA biopolymer NPs for the induction of osteogenic differentiation of hADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, studies showed that the degradation of polylactic acid (PLA) biopolyester materials is relatively fast, while the degradation of polyhydroxyalkanoate (PHA) is relatively slow [20]. And human adipose derived stem cells (hADSCs) as seed cells are also a potential candidate for osteogenesis differentiation [21][22][23][24], which have been obtained more easily from subcutaneous tissue and widely employed in engineered tissue. These studies inspired us to design a novel long-acting BMPs release system based on PLA and PHA biopolymer NPs for the induction of osteogenic differentiation of hADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…After activation with calcium ions [ 35 ], a dense fibrin rich matrix is formed. When placed in an osseous defect, cells will invade and migrate along the PRGF scaffold [ 21 , 36 , 37 , 38 ], to achieve healing [ 38 , 39 ]. PRGF has been demonstrated to support re-vascularization of mucosa and bone, modulate the inflammation, significantly speed bone healing, and maintain bone volume after surgical interventions [ 35 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have explored the regenerative potential of terminally differentiated cells, e.g., osteoblasts [63,64], most research on cranial bone healing has been conducted with adult stem cells, mainly adipose-and bone marrow-derived stem cells, but also with muscle-, periodontal ligament-, neural crest-, cranial suture-and human dental pulp-derived stem cells, among others [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Collectively, most studies have reported the superior ability of adult stem cells to heal critical size calvarial defects compared with implantation of carriers or scaffolds lacking cells [65,66,73,75,[77][78][79]. A study conducted on rabbit calvaria showed that the regeneration ability of bone marrow-derived stem cells is similar to that achieved by autologous bone [80].…”
Section: Research On Cell-based Strategiesmentioning
confidence: 99%